Solve using the zero-factor proper (13x + 7)(6x – 7) = 0​

Question

Solve using the zero-factor proper (13x + 7)(6x – 7) = 0​

in progress 0
Minh Khuê 3 months 2021-08-25T17:10:53+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-25T17:11:57+00:00

    Answer is x=7/13 and x7/6

    0
    2021-08-25T17:12:28+00:00

    Answer:

    x = -7/13 and x = 7/6

    Step-by-step explanation:

    Using the zero factor property, set each factor equal to zero, and solve for x:

    13x + 7 = 0

    13x = -7

    x = -7/13

    Solve the other factor:

    6x – 7 = 0

    6x = 7

    x = 7/6

    So, the solutions are x = -7/13 and x = 7/6

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )